Monitoring sun bears and Asiatic black bears with remotely sensed predictors to inform conservation management. Issue 1 (27th January 2021) - Scotson, Lorraine; Ross, Steven; Arnold, Todd W.
Abstract: Asiatic black bear Ursus thibetanus and sun bear Helarctos malayanus populations are declining throughout South-east Asia as a result of habitat loss and human disturbance. Knowledge of the distribution and status of each species is limited and largely anecdotal. Range maps are coarse, compiled by expert opinion, and presence or absence is unknown over large portions of South-east Asia. These two species co-occur in Lao People's Democratic Republic and may be faring better there than in neighbouring countries. During 2010–2013 we searched for bear sign along 99 transects within eight study sites throughout Lao. To explore countrywide relative abundance and habitat suitability, we modelled bear sign as a log-linear function of biological and anthropogenic predictors that were associated with habitat assemblages and human disturbance. Bears favored higher elevations and rugged terrain in areas less accessible to humans, and were most abundant in the north and east of Lao. Suitable habitats were rare in the southern lowland plains where bear abundance was relatively low. Our model predicted that Nam Et–Phou Louey National Protected Area had the largest areas of suitable bear habitat, followed by the Nakai-Nam Teun and Nam Ha National Protected Areas. Using transects to survey for bear sign, we created a replicable geographical information system based assessment tool for bears in Lao that can be used to identify conservation opportunities and monitor changes in bear distribution over time.